Farmers typology and crops sustainability in Alto Urubamba, La Convencion – Cusco - Merma, Isaías (2012)
The research was conducted in the geographical region of Alto Urubamba, province of La Convencion, Cusco - Peru. The objective was to identify types of farmers and evaluate crops sustainability on farms of high forest. Surveys were applied to a sample of 106 farmers in both biophysical and socio-economic terms in order to identify typology; this information was analyzed through descriptive statistics. Multivariate analysis using preselected variables was performed to identify types of farmers. In addition, sustainability of eight tropical crops was evaluated; for this purpose, three farms for each crop were selected from 24 evaluated farms. Practical indicators of soil quality and crop health with a valuation from 0 to 10 were used; farmers participated during this evaluation. The results show that there are three types of farmers according to their efficiency in resources management and their economic logic. The crops of tea (6.65) and mango (6.50) obtained the highest values of sustainability, followed by coffee (6.25), cocoa (6.25), citrus (5.50), banana (5.45) and coca (5.10). Papaya (4.60) shows a value less than five; therefore, is considered as unsustainable according to local conditions.